Learning interest in English among nursing students through e-modules - Suryati, Ni Wayan Novi; Dewi, Kadek Maya Cyntia; Rusanti, Putu; Susandi, Ni Kadek Ary; Susanta, I Putu Agus Endra; Wismadewi, I Gusti Agung Galuh (Indonesian Research Journal in Education |IRJE|, 2026)
This study aimed to describe nursing students’ interest in learning English through e-modules in an English for Nurses course. A descriptive quantitative design was employed involving 66 fourth-semester students of the Bachelor of Nursing Study Program at Institut Teknologi dan Kesehatan Bali. The participants were selected through total sampling because all students enrolled in the course were involved in the study. Data were collected using a closed-ended questionnaire consisting of 20 statements covering four indicators of learning interest: enjoyment, involvement, interest, and attention. The responses were analyzed using descriptive statistics and converted into percentage scores. The findings showed that students’ learning interest in using e-modules was categorized as very high. The attention indicator obtained the highest score at 86.4%, followed by enjoyment and interest, each at 81.4%, while involvement reached 80.6%. The average percentage across the four indicators was 82.45%, indicating that students responded positively to the use of e-modules in English learning. These findings suggest that e-modules are suitable learning media for supporting nursing students’ interest in English for Nurses, particularly because they provide flexible access, structured materials, and opportunities for independent learning.